MATLAB Simulation of UAV 3D Path Planning Research Based on ACO Algorithm, Astar Algorithm and RRT Algorithm - Liu, Muling; Liu, Jianbin; Lan, Qingye; Lu, Zhangcheng; Zhang, Wei; Zou, Guangxiong (2024 3rd International Symposium on Semiconductor and Electronic Technology (ISSET), 2024)
UAVs have a wide range of applications in industrial engineering. Three-dimensional path planning is one of the key directions of UAV research. In this paper, the ACO algorithm, Astar algorithm and RRT algorithm are used to simulate multiple obstacles Environment. Through the comparison of simulation results, the influence of algorithm selection on the 3D path planning of UAV in multi-obstacle environment is obtained.